Pneumonia associated with the mechanical ventilation in children and adolescents - Enrique Céspedes Floirian; Dámaris Lisset Borrego Fornaris; Ernesto Gustavo Polanco Chong; Elisa Juy Aguirre; Lisbety Rodríguez Sugv (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The pneumonia associated with the mechanical ventilation is an infection that is related to the sanitary cares.  Objective: To characterize clinical and epidemiologically children and adolescents with pneumonia associated with the mechanical ventilation, according to selected variables.  Method: A descriptive and cross-sectional study of 36 patients with pneumonia associated with mechanical ventilation admitted in the Intensive Cares Unit of Dr. Juan de la Cruz Martínez Maceira Northern Children Hospital; was carried out in Santiago de Cuba, from January, 2017 to December, 2018.  Results: There was a prevalence of the patients under 5 years (80.6 %), the male sex (66.7 %), the long lasting mechanical ventilation (69.4 %) and pneumonias associated with the ventilation of late appearance related to mortality. The most frequent microorganisms were the Gram negative. The combination of cephalosporins and vancomycin were the most used.   Conclusions: The clinical course of the patients depended on the time of beginning, the predominant microorganism and the antimicrobial treatment used.